Extracellular nucleotide signaling in solid organ transplantation. Issue 3 (4th November 2019) - Yeudall, Scott; Leitinger, Norbert; Laubach, Victor E.
Abstract : The role of extracellular purine nucleotides, including adenosine triphosphate (ATP) and adenosine, as modulators of posttransplantation outcome and ischemia‐reperfusion injury is becoming increasingly evident. Upon pathological release of ATP, binding and activation of P2 purinergic surface receptors promote tissue injury and inflammation, while the expression and activation of P1 receptors for adenosine have been shown to attenuate inflammation and limit ischemia‐induced damage, which are central to the viability and long‐term success of allografts. Here we review the current state of the transplant field with respect to the role of extracellular nucleotide signaling, with a focus on the sources and functions of extracellular ATP. The connection between ischemia reperfusion, purinergic signaling, and graft preservation, as well as the role of ATP and adenosine as driving factors in the promotion and suppression of posttransplant inflammation and allograft rejection, are discussed. We also examine novel therapeutic approaches that take advantage of the ischemia‐reperfusion‐responsive and immunomodulatory roles for purinergic signaling with the goal of enhancing graft viability, attenuating posttransplant inflammation, and minimizing complications including rejection, graft failure, and associated comorbidities. Abstract : This minireview provides a concise summary of the current state of the transplant field with respect to the role of extracellular nucleotide signaling, with particular focus on the sources and functions of extracellular ATP.